Magnetic flux inversion in charged BPS vortices in a Lorentz-violating Maxwell-Higgs framework - Casana, R.; Ferreira, M. M.; da Hora, E.; Miller, C. [UNESP] (Elsevier B.V., 2012)
We demonstrate for the first time the existence of electrically charged BPS vortices in a Maxwell-Higgs model supplemented with a parity-odd Lorentz-violating (LV) structure belonging to the CPT-even gauge sector of the standard model extension and a fourth order potential (in the absence of the Chern-Simons term). The modified first order BPS equations provide charged vortex configurations endowed with some interesting features: localized and controllable spatial thickness, integer flux quantization, electric field inversion and localized magnetic flux reversion. This model could possibly be applied on condensed matter systems which support charged vortices carrying integer quantized magnetic flux, endowed with localized flipping of the magnetic flux. (C) 2012 Elsevier B.V. All rights reserved.